Effectivity comparison between three different enamel remineralizing agent postfix orthodontic treatment - Ari Triwardhani, - (Medicina Oral S.L, 2019)
Background: This study aims to compare the effectiveness of topical fluoride application, a toothpaste containing synthetic hydroxyapatite with one containing calcium sodium phosphosilicate (CSPS) in remineralizing enamel after the debonding process. Material and Methods: The study constituted experimental laboratory research incorporating posttest-only control group design. A metal bracket was placed on the buccal surface of 40 premolar teeth and immersed in artificial saliva. After 1 month, the bracket was debonded. The teeth were then randomly divided into four groups, namely (n= 6) the control group (C), the 1st treatment group (T1), the 2nd treatment group (T2), and the 3rd treatment group(T3). There was no treatment of C group. For the T1 group, topical application of fluoride was conducted. For the T2 group, toothpaste containing synthetic hydroxyapatite was applied by brushing the teeth twice a day. The same treatment was administered to the T3 group, but using a different toothpaste containing CSPS. After a treatment of 14 days, the T1, T2, and T3 groups were prepared before being observed with a scanning electron microscope (SEM). The SEM data were examined visually and scored using an enamel surface index (ESI), an enamel damage index (EDI), and an enamel remineralization index. The data obtained were analyzed by means of Kruskal–Wallis and Mann–Whitney tests. The statistical significance value was P < 0.05. Results: A review of the ESI and IRE scores showed that, compared to the C group, all treatment groups recorded a significantly lower score, with T2 registering the lowest. With regard to the EDI scores, only the T1 group showed no significant difference to the C group. Conclusions: Sensitive toothpaste containing synthetic hydroxyapatite and CSSP proved to be more effective in forming the remineralization layer on tooth surfaces compared to topical fluoride application.